PENGARUH NET FOREIGN FUND, HARGA EMAS, SUKU BUNGA TERHADAP IHSG DI BEI PADA MASA PANDEMI COVID-19 - Sukri, Ni Nyoman; Abundanti, Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.02.TAHUN.2023DO - 10.24843/EEB.2023.v12.i02.p06, 2023)
The capital market in Indonesia has an important role in the country's economy. The purpose of this study was to determine the effect of net foreign funds, gold prices and interest rates on the Composite Stock Price Index. This research was conducted on the value of the entire Composite Stock Price Index on the Indonesia Stock Exchange during the COVID-19 pandemic. The sample selection method used is saturated sampling for the entire population. The sample for each variable in this study was 21 data. The analysis used is multiple linear regression analysis. The results showed that net foreign funds had a positive and significant effect on the JCI. The price of gold has a negative and significant effect on the JCI. Interest rates have a negative and significant effect on the JCI. The implication of this research is that this research is expected to provide an empirical contribution to the effect of net foreign funds, gold prices and interest rates on the JCI. Investors need to pay attention to factors that can affect JCI performance during the COVID-19 pandemic, such as net foreign funds, gold prices and interest rates because these factors have a significant influence on the JCI